Loss of hnRNP A1 in murine skeletal muscle exacerbates high-fat diet-induced onset of insulin resistance and hepatic steatosis. (6th June 2019) - Zhao, Mingxia; Shen, Lihong; Ouyang, Zijun; Li, Manru; Deng, Guoliang; Yang, Chenxi; Zheng, Wei; Kong, Lingdong; Wu, Xuefeng; Wu, Xudong; Guo, Wenjie; Yin, Ye; et al.
Abstract: Impairment of glucose (Glu) uptake and storage by skeletal muscle is a prime risk factor for the development of metabolic diseases. Heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1) is a highly abundant RNA-binding protein that has been implicated in diverse cellular functions. The aim of this study was to investigate the function of hnRNP A1 on muscle tissue insulin sensitivity and systemic Glu homeostasis. Our results showed that conditional deletion of hnRNP A1 in the muscle gave rise to a severe insulin resistance phenotype in mice fed a high-fat diet (HFD). Conditional knockout mice fed a HFD showed exacerbated obesity, insulin resistance, and hepatic steatosis. In vitro interference of hnRNP A1 in C2C12 myotubes impaired insulin signal transduction and inhibited Glu uptake, whereas hnRNP A1 overexpression in C2C12 myotubes protected against insulin resistance induced by supraphysiological concentrations of insulin. The expression and stability of glycogen synthase ( gys1 ) mRNA were also decreased in the absence of hnRNP A1. Mechanistically, hnRNP A1 interacted with gys1 and stabilized its mRNA, thereby promoting glycogen synthesis and maintaining the insulin sensitivity in muscle tissue. Taken together, our findings are the first to show that reduced expression of hnRNP A1 in skeletal muscle affects the metabolic properties and systemic insulin sensitivity by inhibiting glycogen synthesis.